Assessment of heavy metal pollution, distribution and source apportionment in the sediment from Feni River estuary, Bangladesh. (July 2018) - Islam, Md. Saiful; Hossain, M. Belal; Matin, Abdul; Islam Sarker, Md. Shafiqul
Abstract: Heavy metal pollution in sediment resources may pose serious threat to ecosystem and human health through food web. In this study, surface sediment samples of 10 stations along the Feni River estuary were analyzed to profile the accumulation, sources and pollution levels of heavy metals. The results revealed that the average contents (μg g −1 ) of eight selected heavy metals followed the order of Mn (37.85) > Cr (35.28) > Ni (33.27) > Co (31.02) > Pb (6.47) > Ag (1.09) > As (0.85) > Hg (0.71), and the concentrations varied spatially and seasonally with relatively higher levels at upward stations and during the rainy season. According to sediment quality guidelines (SQGs), the sediment samples were heavily contaminated with Ag and Hg, and moderately with Co. Threshold effect concentration (TEC) and probable effect concentration (PEC) values indicated that the concentration of only Ni and Cr were likely to occasionally exhibit adverse effects on the ecosystem. Enrichment factor (EF), geo-accumulation index (Igeo ) and contamination factor (CF) analyses revealed that Ag, Co and Hg were at moderate to high pollution levels and the rests (As, Cr, Ni, Pb and Mn) were at no to low pollution levels. Potential ecological risk index (PERI) also showed that Ag, Co and Hg were the most potential ecological risk factor being determined in this studied area. Correlation matrix combined with multivariate principal component analysis and cluster analysis suggest that Ag, Co, Ni and Hg originated from anthropogenic sources (agrochemicals, silver nanoparticles anti-microbial agent, silver plating), whereas As, Cr, Pb and Mn primarily originated from natural geological background. Highlights: EF, Igeo, CF and PERI were used to profile pollution levels of heavy metals in sediments of the Feni River estuary. Ag, Co, Hg and Ni enrichment was more in sediments. Ag and Co were above average shale values; however, Ni exceeded the TEC values. Ag, Co and Ni threats to aquatic ecosystem should not be ignored.